Evidence of lifestyle interventions in a pregnant population with chronic hypertension and/or pre-existing diabetes: a systematic review and narrative synthesis - Goddard, L; Patel, R; Astbury, NM; Tucker, K; McManus, R (Elsevier, 2022)
Background Pregnant people with chronic hypertension, pre-existing diabetes or both are at high risk of developing cardiovascular disease. Lifestyle interventions play an important role in disease management in non-pregnant populations.